Hubungan Efikasi Diri, Gaya Hidup, dan Dukungan Keluarga dengan Hipertensi pada Anggota Prolanis di Wilayah Kerja Puskesmas Oesapa Kota Kupang - Lewa, Maria Dominika Wona; Bunga, Eryc Z. Haba; Gustam, Tasalina Yohana Parameswari; Weraman, Pius (Corona: Jurnal Ilmu Kesehatan Umum, Psikolog, Keperawatan dan Kebidanan, 2025)
Hypertension remains a major health problem with high prevalence, often linked to poor lifestyle habits and low self-efficacy in managing one’s health. Effective hypertension management requires not only support from health professionals but also encouragement from family members who can remind patients to adhere to treatment and provide emotional support. This study aimed to analyze the relationship between self-efficacy, lifestyle, and family support with hypertension among Prolanis members in the working area of Puskesmas Oesapa, Kupang City. Using an observational analytical approach with a cross-sectional design, the study involved 65 hypertensive Prolanis members selected through simple random sampling. Data collection was conducted using a structured questionnaire. The findings showed significant relationships between self-efficacy, physical activity, and diet with hypertension status (p-value = 0.000). However, resting habits were not significantly associated with hypertension (p-value = 0.063), and family support also showed no significant relationship (p-value = 0.388). The study recommends that the Puskesmas continue to strengthen Prolanis activities and enhance health education, particularly regarding the importance of maintaining a healthy lifestyle through proper dietary management and regular light physical activity tailored to the abilities of Prolanis members.